Porous carbon / vanadium nitride composite electrode material and preparation method and application thereof

By using amino-containing interpenetrating network polymers for pyrolytic preparation, the problems of low energy density of supercapacitors and poor cycle life of vanadium nitride are solved, and safe and efficient preparation of porous carbon/vanadium nitride composite electrode materials are achieved. Improves electrochemical performance and cycle life.

CN119446797AActive Publication Date: 2025-02-14NINGXIA UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411636281.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing supercapacitors have low energy density and poor cycle life of vanadium nitride electrode materials. There are safety risks when using reducing atmosphere during the preparation process.

Method used

The amino group-containing interpenetrating network polymer is used as the precursor to prepare porous carbon/vanavan nitride composite electrode material by pyrolysis, avoiding the use of reducing atmospheres such as ammonia and hydrogen to ensure the safety of the preparation environment.

Benefits of technology

The prepared porous carbon/vanavan nitride composite electrode material has excellent cycle life and improves electrochemical activity and conductivity, ensuring the safety of the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446797A_ABST
    Figure CN119446797A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon / vanadium nitride composite electrode material and a preparation method and application thereof, and belongs to the technical field of electrode materials. The preparation method of the porous carbon / vanadium nitride composite electrode material comprises the following steps: taking an amino-containing interpenetrating network polymer as a precursor, removing moisture, and carrying out impregnation complexation with vanadium oxide sol to obtain an impregnated compound after impregnation is completed; and performing primary pyrolysis on the impregnated compound at the temperature of 280-350 DEG C in a protective atmosphere, and then performing secondary pyrolysis at the temperature of 700-900 DEG C to prepare the porous carbon / vanadium nitride composite electrode material. During preparation, a reducing atmosphere does not need to be introduced, the preparation environment is safe, and the prepared porous carbon / vanadium nitride composite electrode material is excellent in cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and more specifically to a porous carbon / vanadium nitride composite electrode material and a preparation method and application thereof. Background Art

[0002] Electrochemical energy storage devices include rechargeable batteries and capacitors. Rechargeable batteries usually have high energy density, but their long charge and discharge time and poor cycle performance limit their widespread application. Traditional capacitors have extremely high specific power, but their storage capacity is not ideal. New energy storage devices, electrochemical capacitors, also called supercapacitors, have higher specific power than lithium-ion batteries and better energy density than traditional capacitors. They also have outstanding advantages such as short charging time, wide operating temperature range, long cycle life, safety and environmental friendliness. They have been widely studied in new energy vehicles, aerospace, sensors and other fields.

[0003] At present, the energy density of supercapacitors is low, which limits their development. The main methods to improve their energy density are to increase the specific capacitance of electrode materials and expand their potential window. The supercapacitor electrode materials that researchers have studied more are transition metal oxides such as RuO 2 、MnO 2 、V 2 O 5 etc., they have higher theoretical specific capacity, however, RuO 2 Expensive, other transition metal oxides have poor conductivity. Conductive polymers have high specific capacity and electronic conductivity, but their stability is poor.

[0004] Vanadium nitride is an ideal supercapacitor electrode material due to its wide potential window (-1.2V~0V) and high specific capacitance. However, its cycle life is poor. Composite carbon materials are an effective way to improve their stability. Common composite carbon materials are mainly based on vanadium oxide precursors. Composite carbon materials, such as carbon nanotubes and graphene, need to use a reducing atmosphere, such as hydrogen and ammonia, when sintered in a high temperature environment of 900°C, which poses certain safety risks. Summary of the invention

[0005] In view of the above problems, the present invention provides a porous carbon / vanadium nitride composite electrode material and a preparation method and application thereof. The present invention does not require the introduction of a reducing atmosphere during preparation, the preparation environment is safe, and the prepared porous carbon / vanadium nitride composite electrode material has an excellent cycle life.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a porous carbon / vanadium nitride composite electrode material, comprising the following steps:

[0008] The amino-containing interpenetrating network polymer is used as a precursor, and after removing water, the vanadium oxide sol is impregnated and complexed. After the impregnation is completed, an impregnation composite is obtained.

[0009] The impregnated composite is subjected to a primary pyrolysis at 280°C to 350°C under a protective atmosphere. During the primary pyrolysis, the amino-containing interpenetrating network polymer undergoes a cyclization reaction. Then, a secondary pyrolysis is carried out at 700°C to 900°C. During the secondary pyrolysis, the easily decomposable polymer in the amino-containing interpenetrating network polymer decomposes to produce a pore structure, the difficult-to-decompose polymer is pyrolyzed and cross-linked to form a carbon network structure, CNH bonds and VO bonds are broken and reconstructed to generate vanadium nitride, and vanadium oxide is carbon-thermally reduced to generate vanadium nitride, thereby preparing a porous carbon / vanadium nitride composite electrode material.

[0010] For example, the temperature of the primary pyrolysis may be 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, etc.

[0011] The temperature of secondary pyrolysis can be 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, etc., but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable and will not be repeated here.

[0012] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0013] As a preferred technical solution of the present invention, the ratio of the interpenetrating network polymer to the vanadium oxide is 1.5g to 2g: 2mmol to 3mmol. For example, the ratio of the interpenetrating network polymer to the vanadium oxide can be 1.5g: 2mmol, 1.5g: 2.2mmol, 1.5g: 2.4mmol, 1.5g: 2.6mmol, 1.5g: 2.8mmol, 1.5g: 3mmol, 1.7g: 2mmol, 1.7g: 2.2mmol, 1.7g: 2.4mmol, 1.7g: 2.6mmol, 1.7g: 2.8mmol, 1.7g: 3mmol, 1g: 1mmol, 1g: 1.1mmol, 1g: 1.2mmol, 1g: 1.3mmol, 1g: 1.4mmol, 1g: 1.5mmol, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable, so they will not be repeated here one by one.

[0014] As a preferred technical solution of the present invention, the time of secondary pyrolysis is 2h to 4h. For example, the time of secondary pyrolysis can be 2h, 2.4h, 2.8h, 3.2h, 3.6h, 4h, etc., but it is not limited to the listed values. Other values ​​not listed in the above numerical range are also applicable, and they will not be repeated here.

[0015] As a preferred technical solution of the present invention, the time of a pyrolysis is 2h to 4h. For example, the time of a pyrolysis can be 2h, 2.4h, 2.8h, 3.2h, 3.6h, 4h, etc., but it is not limited to the listed values. Other values ​​not listed in the above numerical range are also applicable, and they will not be repeated here.

[0016] As a preferred technical solution of the present invention, the immersion time is 6h to 12h. It is understandable that as the immersion time increases, the vanadium oxide sol solution absorbs more. For example, the immersion time can be 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, etc., but is not limited to the listed values. Other values ​​not listed in the above numerical range are also applicable, and will not be repeated here.

[0017] As a preferred technical solution of the present invention, the preparation steps of vanadium oxide sol are: dispersing vanadium oxide in water, adding H 2 O 2 and NaCl to obtain vanadium oxide sol.

[0018] As a preferred technical solution of the present invention, the ratio of vanadium oxide to water is 1 mmol to 1.5 mmol:30 mL; for example, the ratio of vanadium oxide to water is 1 mmol:30 mL, 1.1 mmol:30 mL, 1.2 mmol:30 mL; 1.3 mmol:30 mL, 1.4 mmol:30 mL, 1.5 mmol:30 mL, etc.

[0019] Water and H 2 O 2 The volume ratio of water and H is 12:1 to 1.2; for example, 2 O 2 The volume ratio is 12:1, 12:1.1, 12:1.2, etc.

[0020] The ratio of vanadium oxide to NaCl is 2mmol to 3mmol: 1.2g to 1.4g. For example, the ratio of vanadium oxide to NaCl is 2mmol: 1.2g, 2mmol: 1.3g, 2mmol: 1.4g, 2.5mmol: 1.2g, 2.5mmol: 1.3g, 2.5mmol: 1.4g, 3mmol: 1.2g, 3mmol: 1.3g, 3mmol: 1.4g, etc., but it is not limited to the listed values. Other values ​​not listed in the above numerical range are also applicable, and they will not be repeated here.

[0021] As a preferred technical solution of the present invention, the interpenetrating network polymer is polyvinyl alcohol / polyacrylamide interpenetrating network polymer, polyvinyl pyrrolidone / polyacrylamide interpenetrating network polymer, polyvinyl alcohol / chitosan interpenetrating network polymer or polyvinyl pyrrolidone / chitosan interpenetrating network polymer.

[0022] In a second aspect, the present invention provides a porous carbon / vanadium nitride composite electrode material prepared by the above preparation method.

[0023] In a third aspect, the present invention provides the use of the above-mentioned porous carbon / vanadium nitride composite electrode material in the preparation of a supercapacitor.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention uses an amino-containing interpenetrating network polymer to perform pyrolysis to prepare a porous carbon material under a protective atmosphere, and the presence of the amino group can decompose and spontaneously generate an ammonia atmosphere for reducing vanadium oxide to generate vanadium nitride or breaking the NH bond and combining with VO to prepare a porous carbon / vanadium nitride composite material. The method of the present invention avoids the use of a reducing atmosphere such as ammonia and hydrogen, and is a new method for safely preparing a porous carbon / vanadium nitride composite material in a protective gas environment.

[0026] Compared with the traditional VN material, when the porous carbon / vanadium nitride composite material is prepared in the present invention, the presence of V during the pyrolysis process increases the orderliness of the local carbon material and the degree of graphitization, causing I G The increase in I D / I G The conductivity of the composite material is reduced and improved, thereby improving electron transfer; the presence of pores is conducive to the full wetting and mass transfer of the electrolyte; the vanadium nitride nanoparticles and pore structure increase the contact area between the electrode material and the electrolyte; ultimately, the electrochemical activity of the porous carbon / vanadium nitride composite material is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1are scanning electron microscope images, transmission electron microscope images and element distribution diagrams of different samples, wherein a is a scanning electron microscope image of the NPC prepared in comparative example 2, b is a scanning electron microscope image of the VN / NPC prepared in example 1, c is a transmission electron microscope image of the VN / NPC prepared in example 1 at a scale of 100 nm, d is a transmission electron microscope image of the VN / NPC prepared in example 1 at a scale of 20 nm, the inset in figure d is a pore size distribution diagram of the VN / NPC prepared in example 1, e is a transmission electron microscope image of the VN / NPC prepared in example 1 at a scale of 20 nm, the inset in figure e is a particle size distribution diagram and a crystal plane spacing diagram of the VN / NPC prepared in example 1, and f is a distribution diagram of different elements.

[0028] Figure 2 XRD pattern of VN / NPC prepared in Example 1 (a) and Raman spectra of different composite materials (b).

[0029] Figure 3 Figure 2 is the electrochemical properties of different composite materials, where a is the cyclic voltammetry curve, b is the charge-discharge curve, and c is the specific capacitance.

[0030] Figure 4 Figures 1 and 2 are scanning electron microscope images, XRD images and electrochemical properties of different samples, wherein a is a scanning electron microscope image of NPC-CS prepared in comparative example 4, b is a scanning electron microscope image of VN / NPC-PVACS prepared in Example 6, c is an XRD image of VN / NPC-PVACS prepared in Example 6, d is a cyclic voltammetry curve of the materials prepared in Example 6 and comparative example 4, e is a charge-discharge curve of the materials prepared in Example 6 and comparative example 4, and f is the specific capacitance of the materials prepared in Example 6 and comparative example 4. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] As shown in the background technology, the current method for preparing powdered vanadium nitride is mainly to prepare metal oxide precursors at high temperature under a reducing atmosphere (hydrogen, ammonia, etc.). Ammonia and hydrogen, etc., pose safety hazards. The present invention proposes a method for preparing a porous carbon / vanadium nitride composite electrode material, which avoids the use of hazardous gases during the preparation process. The specific technical solution is as follows.

[0033] A method for preparing a porous carbon / vanadium nitride composite electrode material comprises the following steps:

[0034] The amino-containing interpenetrating network polymer gel is used as a precursor, and after freeze drying to remove water, the vanadium oxide sol solution is impregnated and absorbed. After the impregnation is completed, an impregnation composite is obtained, and then freeze drying is performed.

[0035] The frozen impregnation composite is subjected to a primary pyrolysis at 280°C to 350°C under a protective atmosphere, and then the temperature is continuously raised to 700°C to 900°C for a secondary pyrolysis to obtain a porous carbon / vanadium nitride composite electrode material.

[0036] The present invention is to construct an interpenetrating network polymer hydrogel containing amino groups, freeze-dry it, and this freeze-drying step can keep the framework structure in the hydrogel from being damaged; soak it in vanadium oxide sol, the amino groups in the dry gel serve as active sites, and the vanadium oxide ions are fully absorbed due to the hydrogen bond effect, and the solute in the aqueous solution can be evenly dispersed in the gel, and the NaCl can be used as a salt template and can be washed off later to obtain the interpenetrating network polymer / vanadium oxide / NaCl hydrogel. After freeze-drying again, its solid particles will precipitate and be fixed on the surface of the dry gel; thereafter, a pyrolysis treatment is carried out at 280°C to 350°C. Within this temperature range, the polymer will undergo a cyclization reaction to form a more stable structure. These stable structures can be better retained at subsequent high temperatures, thereby increasing the residual carbon content to a certain extent. In addition, some small molecules are decomposed in advance, and then a secondary pyrolysis treatment is carried out at 700°C to 900°C. The easily decomposable polymers in the interpenetrating network polymer are decomposed to produce a pore structure, and the difficult-to-decompose polymers are pyrolyzed and cross-linked into a carbon network structure. The CNH in the amino group breaks and undergoes high-temperature reconstruction with the broken VO to generate vanadium nitride. In addition, the carbon network structure is also thermally reduced at high temperature to prepare vanadium nitride from VO compounds, and finally a porous carbon / vanadium nitride composite material is obtained.

[0037] Further, the interpenetrating network polymer is a polyvinyl alcohol / polyacrylamide interpenetrating network polymer, a polyvinyl pyrrolidone / polyacrylamide interpenetrating network polymer, a polyvinyl alcohol / chitosan interpenetrating network polymer or a polyvinyl pyrrolidone / chitosan interpenetrating network polymer. The present invention has no particular limitation on the source of the interpenetrating network polymer, and those skilled in the art can select and adjust it according to actual application conditions, product quality and product performance.

[0038] The preparation method of polyvinyl alcohol / polyacrylamide interpenetrating network polymer is as follows:

[0039] 2 g of polyvinyl alcohol (PVA) was placed in 20 mL of deionized water and stirred at 90 °C until transparent, then 2 g of acrylamide monomer was added, and after stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N,N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 °C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, polyvinyl alcohol / polyacrylamide interpenetrating network polymer hydrogel was obtained, which was recorded as PVA / PAM IPNs hydrogel.

[0040] The preparation method of polyvinyl pyrrolidone / polyacrylamide interpenetrating network polymer is as follows:

[0041] 2 g of polyvinylpyrrolidone (PVP) was placed in 20 mL of deionized water and stirred at 90 °C until transparent, then 2 g of acrylamide monomer was added, and after stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N,N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 °C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, polyvinylpyrrolidone / polyacrylamide interpenetrating network polymer hydrogel was obtained, which was recorded as PVP / PAM IPNs hydrogel.

[0042] The preparation method of polyvinyl alcohol / chitosan interpenetrating network polymer is as follows:

[0043] 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 °C until transparent. Then 2 g of chitosan was added. After stirring, 10 mg of the oxidant ammonium persulfate and 2 mg of the cross-linking agent N,N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 °C for 3 h to complete the free radical polymerization of the acrylamide monomer. After repeated freezing and thawing three times, a polyvinyl alcohol / chitosan interpenetrating network polymer hydrogel was obtained, which was recorded as PVA / CS IPNs hydrogel.

[0044] The preparation method of polyvinyl pyrrolidone / chitosan interpenetrating network polymer is as follows:

[0045] 2 g of PVP was placed in 20 mL of deionized water and stirred at 90 °C until transparent. Then 2 g of chitosan was added. After stirring, 10 mg of the oxidant ammonium persulfate and 2 mg of the cross-linking agent N,N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 °C for 3 h to complete the free radical polymerization of the acrylamide monomer. After repeated freezing and thawing three times, a polyvinyl pyrrolidone / chitosan interpenetrating network polymer hydrogel was obtained, which was recorded as PVP / CS IPNs hydrogel.

[0046] It should be noted that the molecular weight of PVA used in the present invention is 80,000 and the degree of polymerization is 1,799. The molecular weight of chitosan is 70w to 80w, and the molecular weight of PVP is 58,000. The vanadium oxide used in the present invention is vanadium pentoxide, denoted as V 2 O 5 .

[0047] Example 1

[0048] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent, then 2 g of acrylamide monomer was added, and after stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, a polyvinyl alcohol / polyacrylamide interpenetrating network polymer was obtained, which was recorded as PVA / PAM IPNs hydrogel.

[0049] Step 2: 0.364 g of V 2 O 5 Disperse in 60 mL of water and add 5 mL of H 2 O 2 The solution was stirred for 30 min until it turned orange-red, and then 1.2 g of NaCl was added and stirred for 10 min until it became clear to obtain a vanadium oxide sol solution.

[0050] Step 3, take 1.5g PVA / PAM IPNs hydrogel, immerse it in 60mL vanadium oxide sol solution prepared in step 2, soak it for 12h and then freeze-dry it, then carbonize it at 280℃ for 2h in a nitrogen atmosphere, continue to heat it to 700℃ for 2h, wash and dry it to obtain a porous carbon / vanadium nitride composite electrode material, marked as VN / NPC.

[0051] Example 2

[0052] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent. Then, 2 g of acrylamide monomer was added. After stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVA / PAM IPNs hydrogel was obtained.

[0053] Step 2: 0.364 g of V 2 O 5 Disperse in 60 mL of water and add 5 mL of H 2 O 2The solution was stirred for 30 min until it turned orange-red, and then 1.2 g of NaCl was added and stirred for 10 min until it became clear to obtain a vanadium oxide sol solution.

[0054] Step 3, take 1.5g PVA / PAM IPNs hydrogel, immerse it in 60mL vanadium oxide sol solution prepared in step 2, soak it for 12h and then freeze-dry it, then carbonize it at 280°C for 2h in a nitrogen atmosphere, continue to heat it to 800°C for 2h, and then wash and dry it to obtain a porous carbon / vanadium nitride composite electrode material.

[0055] Example 3

[0056] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent. Then, 2 g of acrylamide monomer was added. After stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVA / PAM IPNs hydrogel was obtained.

[0057] Step 2: 0.364 g of V 2 O 5 Disperse in 60 mL of water and add 5 mL of H 2 O 2 The solution was stirred for 30 min until it turned orange-red, and then 1.2 g of NaCl was added and stirred for 10 min until it became clear to obtain a vanadium oxide sol solution.

[0058] Step 3, take 1.5g PVA / PAM IPNs hydrogel, immerse it in 60mL vanadium oxide sol solution prepared in step 2, soak it for 12h and then freeze-dry it, then carbonize it at 280°C for 2h in a nitrogen atmosphere, continue to heat it to 900°C for 2h, and then wash and dry it to obtain a porous carbon / vanadium nitride composite electrode material.

[0059] Example 4

[0060] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent. Then, 2 g of acrylamide monomer was added. After stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVA / PAM IPNs hydrogel was obtained.

[0061] Step 2: 0.564 g of V 2 O 5Disperse in 60 mL of water and add 6 mL of H 2 O 2 The solution was stirred for 30 min until it turned orange-red, and then 1.3 g of NaCl was added and stirred for 10 min until it became clear to obtain a vanadium oxide sol solution.

[0062] Step 3, take 2g of PVA / PAM IPNs hydrogel, immerse it in 60mL of vanadium oxide sol solution prepared in step 2, soak it for 6h and then freeze-dry it, then carbonize it at 350°C for 3h in a nitrogen atmosphere, continue to heat it to 700°C for 4h, and after washing and drying, a porous carbon / vanadium nitride composite electrode material can be obtained.

[0063] Example 5

[0064] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent. Then, 2 g of acrylamide monomer was added. After stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVA / PAM IPNs hydrogel was obtained.

[0065] Step 2: 0.455 g of V 2 O 5 Disperse in 60 mL of water and add 5.5 mL of H 2 O 2 The solution was stirred for 30 min until it turned orange-red, and then 1.4 g of NaCl was added and stirred for 10 min until it became clear to obtain a vanadium oxide sol solution.

[0066] Step 3, take 1.8g PVA / PAM IPNs hydrogel, immerse it in 60mL vanadium oxide sol solution prepared in step 2, soak for 6 hours and then freeze-dry, then carbonize at 300°C for 4 hours in a nitrogen atmosphere, continue to heat to 700°C for 3 hours, and wash and dry to obtain a porous carbon / vanadium nitride composite electrode material.

[0067] Example 6

[0068] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent, then 2 g of chitosan was added, and after stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h for polymerization. After repeated freezing and thawing three times, a polyvinyl alcohol / chitosan interpenetrating network polymer was obtained, which was recorded as PVA / CS IPNs hydrogel.

[0069] Step 2: 0.364 g of V 2 O 5 Disperse in 60 mL of water and add 5 mL of H 2 O 2 The solution was stirred for 30 min until it turned orange-red, and then 1.2 g of NaCl was added and stirred for 10 min until it became clear to obtain a vanadium oxide sol solution.

[0070] Step 3, take 1.5g PVA / CS IPNs hydrogel, immerse it in 60mL vanadium oxide sol solution prepared in step 2, soak it for 12h and then freeze-dry it, then carbonize it at 280℃ for 2h in a nitrogen atmosphere, continue to heat it to 700℃ for 2h, wash and dry it to obtain a porous carbon / vanadium nitride composite electrode material, marked as VN / NPC-PVACS.

[0071] Example 7

[0072] Step 1: 2 g of polyvinyl pyrrolidone (PVP) was placed in 20 mL of deionized water and stirred at 90 ° C until transparent, then 2 g of acrylamide monomer was added, and after stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVP / PAM IPNs hydrogel was obtained.

[0073] Step 2: 0.564 g of V 2 O 5 Disperse in 60 mL of water and add 6 mL of H 2 O 2 The solution was stirred for 30 min until it turned orange-red, and then 1.2 g of NaCl was added and stirred for 10 min until it became clear to obtain a vanadium oxide sol solution.

[0074] Step 3: Take 2 g of PVP / PAM IPNs hydrogel and immerse it in 60 mL of vanadium oxide sol solution prepared in step 2. After soaking for 10 hours, freeze-dry it and then carbonize it at 350°C for 3 hours in a nitrogen atmosphere. Continue to heat it to 700°C for high-temperature carbonization for 2 hours. After washing and drying, a porous carbon / vanadium nitride composite electrode material can be obtained.

[0075] Example 8

[0076] Step 1: 2 g of PVP was placed in 20 mL of deionized water and stirred at 90 ° C until transparent, then 2 g of chitosan was added, and after stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVP / CS IPNs hydrogel was obtained.

[0077] Step 2: 0.564 g of V 2 O 5 Disperse in 60 mL of water and add 5 mL of H 2 O 2 The solution was stirred for 30 min until it turned orange-red, and then 1.4 g of NaCl was added and stirred for 10 min until it became clear to obtain a vanadium oxide sol solution.

[0078] Step 3: Take 2 g of PVP / PAM IPNs hydrogel and immerse it in 60 mL of vanadium oxide sol solution prepared in step 2. After soaking for 8 hours, freeze-dry it and then carbonize it at 350°C for 2 hours in a nitrogen atmosphere. Continue to heat it to 700°C for high-temperature carbonization for 4 hours. After washing and drying, a porous carbon / vanadium nitride composite electrode material can be obtained.

[0079] Comparative Example 1

[0080] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent. Then, 2 g of acrylamide monomer was added. After stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVA / PAM IPNs hydrogel was obtained.

[0081] Step 2: Add 5 mL of H2O dropwise to 60 mL of water. 2 O 2 Stir for 30 min to obtain a solution.

[0082] Step 3: Take 1.5 g of PVA / PAM IPNs hydrogel and immerse it in 60 mL of the solution prepared in step 2. After soaking for 12 h, freeze-dry it and then carbonize it at 280 ° C for 2 h under a nitrogen atmosphere. Continue to heat it to 700 ° C for high temperature carbonization for 2 h. After washing and drying, a carbon electrode material can be obtained, which is marked as NC.

[0083] Comparative Example 2

[0084] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent. Then, 2 g of acrylamide monomer was added. After stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVA / PAM IPNs hydrogel was obtained.

[0085] Step 2: Add 5 mL of H2O dropwise to 60 mL of water. 2 O 2 The mixture was stirred for 30 min, and then 1.2 g of NaCl was added and stirred for 10 min until a clear solution was obtained.

[0086] Step 3: Take 1.5 g of PVA / PAM IPNs hydrogel and immerse it in 60 mL of the solution prepared in step 2. After soaking for 12 h, freeze-dry it and then carbonize it at 280 ° C for 2 h under a nitrogen atmosphere. Continue to heat it to 700 ° C for high temperature carbonization for 2 h. After washing and drying, a porous carbon electrode material can be obtained, which is marked as NPC.

[0087] Comparative Example 3

[0088] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent. Then, 2 g of acrylamide monomer was added. After stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, and reacted at 60 ° C for 3 h to complete the free radical polymerization of acrylamide monomer. After repeated freezing and thawing three times, PVA / PAM IPNs hydrogel was obtained.

[0089] Step 2: 0.364 g of V 2 O 5 Disperse in 60 mL of water and add 5 mL of H 2 O 2 The mixture was stirred for 30 min to obtain a vanadium oxide sol solution.

[0090] Step 3, take 1.5g PVA / PAM IPNs hydrogel, immerse it in 60mL vanadium oxide sol solution prepared in step 2, soak it for 12h and then freeze-dry it, then carbonize it at 280°C for 2h in a nitrogen atmosphere, continue to heat it to 900°C for 2h, wash and dry it to obtain a porous carbon / vanadium nitride composite electrode material, marked as VN / NC.

[0091] Comparative Example 4

[0092] Step 1: 2 g of PVA was placed in 20 mL of deionized water and stirred at 90 ° C until transparent, then 2 g of chitosan was added, and after stirring, 10 mg of oxidant ammonium persulfate and 2 mg of cross-linking agent N, N'-methylenebisacrylamide were added. The mixed solution was sealed and degassed, reacted at 60 ° C for 3 h for polymerization, and repeatedly frozen and thawed three times to obtain PVA / CS IPNs hydrogel.

[0093] Step 2: Add 5 mL of H2O dropwise to 60 mL of water. 2 O 2 The mixture was stirred for 30 min, and then 1.2 g of NaCl was added and stirred for 10 min until a clear solution was obtained.

[0094] Step 3: Take 1.5 g of PVA / CS IPNs hydrogel and immerse it in 60 mL of the solution prepared in step 2. After soaking for 12 h, freeze-dry it and then carbonize it at 280 ° C for 2 h in a nitrogen atmosphere. Continue to heat it to 700 ° C for high temperature carbonization for 2 h. After washing and drying, a porous carbon electrode material can be obtained, which is marked as NPC-CS.

[0095] In addition, commercial vanadium nitride was purchased as a control group and marked as VN.

[0096] Figure 1 a in the figure is a scanning electron microscope image of NPC, which shows a flake-like morphology. Figure 1 Figure b is a scanning electron microscope image of the prepared VN / NPC, which shows that it is also in the form of thin flakes and the surface has become smooth. Figure 1 Figure c is a transmission electron microscope image of the prepared VN / NPC, which can be seen to be in the form of thin sheets. Figure 1 Figure d is a transmission electron microscope image of the prepared VN / NPC. White dots can also be seen, representing the pore size. The small pore size is concentrated at 2.5 nm. Figure 1 The interplanar spacing of the VN(111) crystal plane can also be clearly identified in e. Figure 1 The f in the figure is the element distribution diagram, from which we can see that the C, N, and V elements in the material are evenly distributed.

[0097] Figure 2 a in the figure is the XRD spectrum of VN / NPC. After comparison, it is VN phase (JCPDF 35-0768). The score around 24° is attributed to carbon material, which proves that VN / NPC material is successfully prepared. Figure 2 b is the Raman spectrum, which clearly shows that the I D / I G Close to 1.20, the composite material VN / NPC is 0.91, mainly because the presence of metal element V during pyrolysis increases the order of local carbon materials and the degree of graphitization, causing I GThe increase in I D / I G decreases, and thus the electrical conductivity of the composite material increases.

[0098] Figure 3 Electrochemical properties of VN, NC, NPC, VN / NC and VN / NPC. Figure 3 The a in the figure is the cyclic voltammetry curve. It can be seen that the shape of the curve is different from the regular rectangular structure. The energy storage of VN is a pseudocapacitive energy storage mechanism. The synthesized VN / NPC has a larger surrounding area than the commercial VN, as well as the NC, NPC, and VN / PC prepared in the process, proving that the prepared VN / NPC has a higher specific capacitance. In addition, Figure 3 The charge-discharge curve of b in Figure 1 also shows that VN / NPC has a longer discharge time. After calculation, Figure 3 As shown in c, the specific capacitance of the composite material at a current density of 0.5A / g is 248.3F / g, which is greater than the specific capacitance of other materials. The specific capacitance of VN at a current density of 0.5A / g is 5.4F / g, the specific capacitance of NC at a current density of 0.5A / g is 22.3F / g, the specific capacitance of NPC at a current density of 0.5A / g is 43.4F / g, and the specific capacitance of VN / NC at a current density of 0.5A / g is 213.7F / g. The reasons for the increase in the specific capacitance of VN / NPC are mainly based on (1) the improvement of conductivity helps to improve electron transfer; (2) the emergence of pore structure helps to fully infiltrate and transfer the electrolyte; (3) vanadium nitride nanoparticles and pore structure help to increase the contact area between the electrode material and the electrolyte; (4) NaCl as an inorganic salt template can increase the specific surface area to a certain extent, and in addition, ensure the stability of the gel in the salt solution. Due to the above four reasons, the porous carbon / vanadium nitride composite material prepared by the present invention has a higher specific capacitance.

[0099] Figure 4 a is a scanning electron microscope image of the carbon material prepared in Example 4 using PVA / CS IPNs hydrogel as a precursor, showing a porous structure. After heat treatment with VO sol solution, i.e. Example 6, Figure 4 As shown in b, its morphology is consistent with that of the carbon material, and its surface is relatively smooth. By testing the XRD of the VN / NPC-PVACS prepared in Example 6, the presence of vanadium nitride and carbon material was found, proving that the present invention successfully prepared the VN / carbon composite material. Figure 4 d in the figure is the cyclic voltammetry curve. The results show that the carbon material presents a relatively regular rectangular structure, while the VN / NPC-PVACS composite material has a peak near -0.6, which is also a manifestation of VN pseudocapacitance. Figure 4 It is obvious from the e in that the composite material has a longer discharge time. After calculation, such as Figure 4In the figure, the specific capacitance of VN / NPC-PVACS is 120F / g at 0.5A / g, which is higher than that of the corresponding prepared carbon materials.

[0100] The VN / NPC prepared in Example 1 was -1 Under the conditions of , after 10000 cycles, the capacitance retention rate is 96.2%, indicating that the composite material has a good cycle life.

[0101] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0102] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a porous carbon / vanadium nitride composite electrode material, characterized in that: The following steps are involved: An amino-containing interpenetrating network polymer is used as a precursor, and after removing water, the precursor is impregnated and complexed with a vanadium oxide sol, and after the impregnation is completed, an impregnation composite is obtained; The impregnated composite is subjected to a primary pyrolysis at 280°C to 350°C under a protective atmosphere. During the primary pyrolysis, the amino-containing interpenetrating network polymer undergoes a cyclization reaction. Then, a secondary pyrolysis is carried out at 700°C to 900°C. During the secondary pyrolysis, the easily decomposable polymer in the amino-containing interpenetrating network polymer decomposes to produce a pore structure, the difficult-to-decompose polymer is pyrolyzed and cross-linked to form a carbon network structure, the NH bonds and VO bonds are broken and reconstructed to generate vanadium nitride, and the vanadium oxide is carbon-thermally reduced to generate vanadium nitride, thereby preparing a porous carbon / vanadium nitride composite electrode material.

2. The method for preparing a porous carbon / vanadium nitride composite electrode material according to claim 1, characterized in that: The ratio of the interpenetrating network polymer to the vanadium oxide is 1.5 g to 2 g: 2 mmol to 3 mmol.

3. The method for preparing a porous carbon / vanadium nitride composite electrode material according to claim 1, characterized in that: The time of secondary pyrolysis is 2h~4h.

4. The method for preparing a porous carbon / vanadium nitride composite electrode material according to claim 1, characterized in that: The time of one pyrolysis is 2h to 4h.

5. The method for preparing a porous carbon / vanadium nitride composite electrode material according to claim 1, characterized in that: The immersion time is 6h to 12h.

6. The method for preparing a porous carbon / vanadium nitride composite electrode material according to claim 1, characterized in that: The preparation steps of vanadium oxide sol are as follows: dispersing vanadium oxide in water, adding H2O2 and NaCl and stirring to obtain vanadium oxide sol.

7. The method for preparing a porous carbon / vanadium nitride composite electrode material according to claim 6, characterized in that: The ratio of vanadium oxide to water is 1 mmol to 1.5 mmol: 30 mL; The volume ratio of water to H2O2 is 12:1 to 1.2; The ratio of vanadium oxide to NaCl is 2 mmol to 3 mmol: 1.2 g to 1.4 g.

8. The method for preparing a porous carbon / vanadium nitride composite electrode material according to claim 1, characterized in that: The interpenetrating network polymer is polyvinyl alcohol / polyacrylamide interpenetrating network polymer, polyvinyl pyrrolidone / polyacrylamide interpenetrating network polymer, polyvinyl alcohol / chitosan interpenetrating network polymer or polyvinyl pyrrolidone / chitosan interpenetrating network polymer.

9. A porous carbon / vanadium nitride composite electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the porous carbon / vanadium nitride composite electrode material according to claim 9 in preparing a supercapacitor.

Citation Information

Patent Citations

  • Preparation method of vanadium oxide nanocomposite of lithium ion battery

    CN103066244A

  • A method of preparing a hierarchical porous carbon material as a supercapacitor electrode material

    CN107098330A

  • Preparation method of vanadium nitride nanoparticle composite material for lithium-sulfur battery

    CN112960656A

  • Porous carbon sphere packaged vanadium oxide heterogeneous core-shell sphere structure material and preparation method thereof, lithium-sulfur battery diaphragm and lithium-sulfur battery

    CN113036311A

  • Hierarchical porous carbon with interpenetrating double aerogel as precursor and preparation method and application thereof

    CN117153577A